Age-Related Hearing Loss With Tinnitus and Physical Frailty Influence the Overall and Domain-Specific Quality of Life of Chinese Community-Dwelling Older Adults - Zhang, Weibin; Ruan, Jian; Zhang, Ruxin; Zhang, Min; Hu, Xiuhua; Yu, Zhuowei; Han, Zhao; Ruan, Qingwei (Frontiers in Medicine, 2021)
Objectives:To investigate the impact of the severity of age-related hearing loss (ARHL) and tinnitus, the presentation of ARHL and/or tinnitus, physical frailty on the health-related quality of life (HRQoL) and domain-specific HRQoL in Chinese community-dwelling older adults. Design: This was a cross-sectional study of a community-based cohort. Participants: We evaluated Chinese older adults (n = 429, 183 men and 246 women) aged≥58years. Measurements: The severity of HL and tinnitus were measured using pure-tone audiometry and the Tinnitus Handicap Inventory (THI), respectively. Physical frailty was measured using the five-item Fried scale. HRQoL was assessed using the Assessment of Quality of Life-8-Dimension (AQoL-8D) multi-attribute utility instrument (35 HRQoL items and 8 domain-specific HRQoL subcategories. Low HRQoL (HRQoL score or subscores in the highest quintile) was used as a dependent variable in logistic regression analyses adjusted for demographic (Model 1) and health-related (Model 2) and psychosocial (Model 3) confounders. Results: ARHL severity was an independent determinant of senses in the physical dimension of HRQoL after adjusting for all covariates. Tinnitus severity was significantly associated with HRQoL and with independent living, senses, and pain in the physical dimension after adjusting for demographic and health-related covariates; and still associated with independent living and senses after adjusting for all covariates. The presentation of ARHL and/or tinnitus was significantly associated with independent living and senses in the physical dimension after adjusting for all covariates. Physical frailty was an independent determinant of HRQoL, independent living, and pain in the physical dimension and with mental health, happiness, and coping in the psychosocial dimension after adjusting for demographic and health-related covariates. The association with HRQoL, independent living, and pain in the physical dimension and with happiness and coping in the psychosocial dimension remained significant after adjusting for covariates. Depressive symptoms, social dysfunction, and number of comorbidities were critical determinants of psychosocial HRQoL. Conclusion: Physical frailty has a stronger and more profound effect on HRQoL, particularly on independent living and pain in the physical dimension and on happiness and coping in the psychosocial dimension. Domain-specific HRQoL should be considered in the management of patients with ARHL with tinnitus and physical frailty.